Determinants of Competitive Advantage Through Firm Performance: A Quantitative Strategic Management Approach - Maman Sulaeman; Diksi Metris; Ahmad Rasyiddin; Rifaatussalwa Hayati (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study aims to analyze the influence of Innovation Capability, Market Orientation, and Resource Capability on Competitive Advantage with Firm Performance as a mediating variable among batik Micro, Small, and Medium Enterprises (MSMEs) in Tangerang Regency. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. A purposive sample of 147 respondents was obtained from a registered population of 247 active batik MSME units as of January 2026. Results reveal that all three antecedent constructs exert significant positive influences on both Firm Performance and Competitive Advantage, with Resource Capability emerging as the strongest predictor. Firm Performance is confirmed as a significant partial mediator in all three indirect pathways from Innovation Capability, Market Orientation, and Resource Capability to Competitive Advantage. These findings provide actionable strategic insights for batik MSME owners, policymakers, and development agencies seeking to strengthen sectoral competitiveness sustainably